2017
DOI: 10.1016/j.antiviral.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccination regimes against Schmallenberg virus infection in IFNAR −/− mice suggest two targets for immunization

Abstract: Schmallenberg virus (SBV) is an RNA virus of the Bunyaviridae family, genus Orthobunyavirus that infects wild and livestock species of ruminants. While inactivated and attenuated vaccines have been shown to prevent SBV infection, little is known about their mode of immunity; specifically, which components of the virus are responsible for inducing immunological responses in the host. As previous DNA vaccination experiments on other bunyaviruses have found that glycoproteins, as well as modified (i.e. ubiquitina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 51 publications
5
22
0
Order By: Relevance
“…The relation between type I IFN and viral spreading has been investigated using seve day old IFNAR(−/−) mice intracerebrally injected with SBV and an NSs deletion mutant, confirming the role of the NSs protein as a modulator, at least indirectly, of the IFN response in vivo [77]. This mouse model has been used to validate attenuated strains as potential vaccines [41], and to test protective immunity induced by the Gc-ecto1 domain and nucleocapsid protein of the virus, showing that these could be valid candidates for the development of subunit vaccines [42]. Wernike et al [43] have also demonstrated the suitability of using Gc as an efficient vaccine in this murine model.…”
Section: Families Included In the Order Bunyaviralesmentioning
confidence: 90%
See 1 more Smart Citation
“…The relation between type I IFN and viral spreading has been investigated using seve day old IFNAR(−/−) mice intracerebrally injected with SBV and an NSs deletion mutant, confirming the role of the NSs protein as a modulator, at least indirectly, of the IFN response in vivo [77]. This mouse model has been used to validate attenuated strains as potential vaccines [41], and to test protective immunity induced by the Gc-ecto1 domain and nucleocapsid protein of the virus, showing that these could be valid candidates for the development of subunit vaccines [42]. Wernike et al [43] have also demonstrated the suitability of using Gc as an efficient vaccine in this murine model.…”
Section: Families Included In the Order Bunyaviralesmentioning
confidence: 90%
“…After SBV infection, mice showed primarily decreased weight loss, ataxia, apathy, but limited mortality [41]. In recent studies, it has been demonstrated that SBV virulence occurs as early as three days post-infection (dpi) and it becomes more severe at day six post-infection as observed by the significant weight loss and viremia [42]. The relation between type I IFN and viral spreading has been investigated using seve day old IFNAR(−/−) mice intracerebrally injected with SBV and an NSs deletion mutant, confirming the role of the NSs protein as a modulator, at least indirectly, of the IFN response in vivo [77].…”
Section: Families Included In the Order Bunyaviralesmentioning
confidence: 99%
“…The most promising DIVA-compatible antigen delivery systems include live attenuated vaccines, DNA-mediated, subunit or live-vectored vaccines [ 94 ]. All those preparations have been developed for SBV [ 63 , 67 , 95 , 96 , 97 ] and some of them were successfully tested in cattle, one of the major target species of SBV ( Table 1 ).…”
Section: Successfully Tested Vaccine Preparationsmentioning
confidence: 99%
“…Thus, DNA-mediated subunit as well as live-vectored vaccines have been developed on the basis of Gc. While DNA-mediated vaccines have only been tested in small animal models until now [ 63 , 96 ], subunit or viral vector vaccines have proved their efficiency in the target species of SBV, specifically cattle [ 63 , 97 ].…”
Section: Successfully Tested Vaccine Preparationsmentioning
confidence: 99%
See 1 more Smart Citation